Option Pricing for Exchange Rate Hedging: Evaluation of Value at Risk, Sharpe Ratio, and Backtesting with Kupiec and Christoffersen Tests - Muhtarulloh, Fahrudin; Humairo, Rd. Ilfah Syarifah; Meiza, Asti (PT Mattawang Mediatama Solution, 2026)
Exchange rate fluctuations are a major source of risk in international transactions. This study evaluates the effectiveness of currency options as hedging instruments using Value at Risk (VaR) and Sharpe Ratio, and assesses risk model accuracy through backtesting using the Kupiec and Christoffersen tests. Monthly closing prices of USD/IDR and MYR/IDR from January 2022 to January 2025 were obtained from Investing.com. Option pricing was calculated using the Garman–Kohlhagen model, while VaR estimation employed variance–covariance and historical methods. The results show that model accuracy varies across methods and currencies. The effectiveness of options as hedging instruments depends on model parameters, option type, and historical data characteristics.